Collaborative Research Pattern of Physics Nobel Laureate Adam Guy Riess: A Scientometric Study - Sedam, Mariraj Vasudev; K, Keshava (Journal of Data Science, Informetrics, and Citation Studies)
The Nobel Prize in Physics has been awarded 114 times to 216 Nobel Laureates between 1901 and 2020. John Bardeen is the only Nobel Laureate who had been awarded the Nobel Prize in Physics twice, in 1956 and 1972. This meant that a total of 215 individuals had received the Nobel Prize in Physics. In the present paper an attempt has been made to know the publication productivity, authorship pattern and channels of communication based on a scientometric study of research publications of Physics Nobel Laureate Adam Guy Riess (2011).
Keywords: Scientometrics; Scientometric Portrait; Nobel Laureates; h-Index; Publication Productivity; Authorship Credit.